The impacts of vitamin D supplementation in adults with metabolic syndrome: A systematic review and meta-analysis of randomized controlled trials - Qi, Kai-Jie; Zhao, Zhong-Tao; Zhang, Wen; Yang, Fang (Frontiers in Pharmacology, 2022)
Background: Studies have shown the association of vitamin D status with the development of metabolic syndrome (MetS), which has attracted an extensive research interest with inconsistent results. Therefore, we hypothesized that vitamin D supplementation (VDS) will benefit adults with MetS. Aims: To test our hypothesis, we performed a meta-analysis to evaluate the effect of VDS on MetS in adults using relevant biomarkers such as anthropometric parameters, blood pressure, blood lipid profile, glycemia, oxidative stress and vitamin D toxicity (VDT). Methods: Randomized controlled trials published in PubMed, Web of Science, Embase and the Cochrane Library between 2012 and 2022 on the effect of VDS on MetS in adults were searched. The language was limited to English. A meta-analysis performed using RevMan 5.4 and Stata 14.0 software, sensitivity analysis, and evaluation of the risk of bias and general quality of the resulting evidence were conducted. Results: Eventually, 13 articles were included in this meta-analysis. Overall, VDS significantly increased the endline serum 25-hydroxyvitamin D levels as compared to the control [MD:17.41, 95% CI: (14.09, 20.73), p < 0.00001]. VDS did not affect waist circumference, body mass index, body fat percentage and VDT biomarkers, but decreased waist-to-hip ratio and blood pressure (p < 0.01). VDS significantly decreased fasting plasm glucose (FPG) [MD: -3.78; 95% CI: (-6.52, -1.03), p = 0.007], but did not affect the levels of blood high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG). Pooled estimate of nine papers indicated a significant reduction of fasting insulin (FI) (p = 0.006), and homeostasis model assessment of insulin resistance (p = 0.0001). The quantitative insulin check index levels were moderately increased (p = 0.007) without any impact on the glycosylated hemoglobin type A1C (HbA1c). For the oxidative stress parameters, VDS significantly lowered the levels of malondialdehyde and hypersensitive C-reactive protein (p < 0.05). Conclusion: Results of this meta-analysis demonstrate that VDS only reduces insulin resistance and hypertension but not the blood lipid profile and HbA1c. It appears that the evidence for the benefit of VDS in adults with MetS is inconclusive. Further clinical studies are still needed.